The Achievement of the quality standard of education in MAN Palangka Raya - Jasiah Jasiah; Masriah Masriah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2018)
MAN Palangkaraya is the partner schools of the ministries of Religious Affairs and the status is very proud achievement, and graduation reach 100% of the National level (UAMMN) and pass the National Exam (UN), and is accredited A.Based on the explanation above, the writer was interested in and choose the title of Education Quality Assurance in MAN Model Palangka Raya. The purpose of this study was to answer the problem of this research How does the achievement of quality standards of education in MAN Palangka Raya.The place of this research is MAN Palangkaraya at Jl.Tjilik Riwut km. 4,5 Palangka Raya. This study used qualitative methods. The data collection did by observation, interview and documentation. The subjects of this research were headmaster and wakamad as an informant, teachers and educators, and alumni. The validity of the data by using trasferbilitas, accountability, reliability, credibility.The results of the research showed that: Implementation of quality assurance in MAN Palangka Raya includes the standard process such as; teachers and educators and competency standards. Achievement of quality assurance in MAN Palangka Raya have been achieved such as monitoring, evaluation, certification, accreditation and national exams both internally and externally is carried out by the relevant agencies such as the Ministry of Religious Affairs and The Central Kalimantan Provincial Education Office. Keywords: Achievement, Quality Standard, Education,